2023
DOI: 10.1021/acs.est.2c06921
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Ferrihydrite–Extracellular Polymeric Substance Coprecipitates Driven by Dissolved Sulfide: Interrelated Effects of Carbon and Sulfur Loadings

Abstract: The association of poorly crystalline iron (hydr)oxides with organic matter (OM), such as extracellular polymeric substances (EPS), exerts a profound effect on Fe and C cycles in soils and sediments, and their behaviors under sulfate-reducing conditions involve complicated mineralogical transformations. However, how different loadings and types of EPS and water chemistry conditions affect the sulfidation still lacks quantitative and systematic investigation. We here synthesized a set of ferrihydrite−organic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
(198 reference statements)
3
8
0
Order By: Relevance
“…Microcosms with the Floodplain Soil showed DOC concentrations that were comparable to the observations in the field, where water-extractable organic carbon was analyzed in similar floodplain soils . Lastly, the Acid Sulfate Soil led to an aqueous phase with high Fe and SO 4 2– , as observed in such environments. …”
Section: Discussionsupporting
confidence: 72%
“…Microcosms with the Floodplain Soil showed DOC concentrations that were comparable to the observations in the field, where water-extractable organic carbon was analyzed in similar floodplain soils . Lastly, the Acid Sulfate Soil led to an aqueous phase with high Fe and SO 4 2– , as observed in such environments. …”
Section: Discussionsupporting
confidence: 72%
“…Although Fe(II)−OM compounds are commonly considered as important Fe(II) species under anoxic conditions, the formation of Fe(II)−OM compounds from Fe(III) reduction has yet to be reported. 16,17,37 In a previous study on the influence of organic acids on Fh sulfidation 16 with the C/ Fe(III) molar ratio and S(−II)/Fe(III) molar ratio lower than in the present study, no Fe(II)−organic complexes were found in the reduction products, as confirmed by LCF analysis. The higher S(−II)/Fe(III) molar ratio in the present study could result in the higher yield of Fe(II), while the higher C/Fe(III) molar ratio allowed more opportunities for the coordination of Fe(II) with OM.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…Particularly rapid Fe­(III) reduction can be initiated by microbially derived sulfide (S­(−II)), with this sulfidation process being a critical Fe redox reaction in sulfate-reducing environments, such as tidal wetlands, coastal floodplain soils, and many groundwater systems. To date, there are limited studies on the sulfidation of Fe­(III) oxide–OM associations, most of which focus on the sulfidation process without exploring the fate of Fe and DOM in the reoxidation process, and DOM dynamics at the molecular level is largely unexplored. Developing the knowledge of the fate of Fe and DOM over the full sulfidation–reoxidation cycle is important because periodic redox fluctuations, rather than just occurring in permanently reducing or oxidizing conditions, commonly occur in natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite sulfidation leads to the formation of secondary iron sulfides, including mackinawite [FeS m ], greigite [Fe 3 S 4 ], and pyrite 34,35,39 . The mechanisms and rates of these reactions, and the potential transformation of secondary iron sulfides to pyrite, are affected by temperature, solution E h and pH, sulfur/iron ratio, magnetite stoichiometry, and the presence of trace metal(loid)s 34,[39][40][41][42][43][44][45][46][47][48] . Moreover, elemental sulfur [S 0 ], a ubiquitous intermediate sulfur species in hydrothermal systems, can strongly affect magnetite pyritization rates and pyrite morphology 34 .…”
mentioning
confidence: 99%
“…Previous studies have not considered the interrelated effects of sulfur species (i.e., sulfide, S 0 , polysulfides) with organic matter (e.g., microbial biomass) that would be present during the hydrothermal sulfidation of biogenic magnetite. Organic matter is known to affect the surface reactivity and aggregation behavior of Fe(III) (oxyhydr)oxides, including magnetite, and secondary iron (mono)sulfides 47,[49][50][51][52][53] . This potentially influences the textural and geochemical characteristics of the resulting pyrite, which commonly serves as a biosignature of sulfur-cycling microorganisms.…”
mentioning
confidence: 99%